What is wrong with the German economy? The case for openness to technology and human capital - Philipp Lamprecht (European Centre for International Political Economy (ECIPE), 2021)
Advanced economies like Germany need to focus more on attracting foreign high-skilled labour and become better at importing foreign technology and business models. This might not sit well with current thinking of economic sovereignty in Berlin, but it is a necessary step for improving technology-penetration, competitiveness and productivity. Supply of high-skilled labour is getting more difficult to obtain and the cost of generating and adopting new ideas is increasing. Policymakers need to create the right conditions to open their markets to foreign technology and high-skilled labour. But openness alone is only a necessary condition - not a sufficient one. Policymakers also need to focus on creating the right environment domestically to attract a specialised and highly-skilled labour force, despite fierce competition from around the globe. The crucial question is to what extent companies make use of innovation capacities that can be obtained from international recruitment. Our analysis focuses on what German policymakers can do to increase openness for, and its attractiveness to, the high-skilled labour. Germany's policy framework should focus on public policy initiatives aimed at increasing the incentives and removing obstacles for firms to attract the global high-skilled labour force. To stay attractive, Germany's policies should also target issues of bottleneck regulation to facilitate field-testing new technologies and to support innovation sandbox processes of companies. And German policies should focus on the regulatory environment, notably the type of regulations that policymakers pursue. Many current regulations in Germany do not sufficiently allow for experimentation of technologies and ideas.
Keywords: 330; Standortwettbewerb; Hochqualifizierte Arbeitskräfte; Technologiepolitik; Deutschland